2022
DOI: 10.2298/ciceq210101018b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of graphene nano-platelets dispersion on the thermo-physical properties of sunflower oil

Abstract: In this article, thermal stability, viscosity, density and surface tension of Graphene nano-platelets dispersed sunflower oil are experimentally determined by varying the Graphene concentration (0.1-1.1wt%) and temperature (40-100?C). The SEM micrograph and the EDS spectra are used to characterize the Graphene. Nanofluids are prepared by ultrasonication technique (two-step method) and the maximum thermal stability of about 280?C is achieved at 1.1wt% Graphene nanofluids. The dynamic viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…With the development of nanotechnology, more and more researchers study lubricating oil nano-additives with anti-friction and wear-resisting characteristics, such as soft metals 4 , 5 , metal compounds 6 9 , organic compounds 10 , 11 , graphite and its interlayer compounds 12 15 , etc. Among them, two-dimensional nano-graphene is more attention 12 , 16 , 17 . A large number of studies 18 23 have shown that the tribological properties of general industrial lubricanting oil can be improved by adding nano-graphene to them.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of nanotechnology, more and more researchers study lubricating oil nano-additives with anti-friction and wear-resisting characteristics, such as soft metals 4 , 5 , metal compounds 6 9 , organic compounds 10 , 11 , graphite and its interlayer compounds 12 15 , etc. Among them, two-dimensional nano-graphene is more attention 12 , 16 , 17 . A large number of studies 18 23 have shown that the tribological properties of general industrial lubricanting oil can be improved by adding nano-graphene to them.…”
Section: Introductionmentioning
confidence: 99%